Care of obstetric nurses with pregnant pregnant women in a municipal maternity in Teresina-PI (Research, Society and Development, 2021)
For birth to occur naturally it is necessary that there are no unnecessary complications or procedures. To avoid complications, nurses should plan a humanized and effective care with individualized care directed to each situation experienced by the woman during all the phases of labor. The study aims to analyze the care of obstetricians with pregnant women in preterm delivery at a maternity hospital in Teresina-PI. This is a qualitative study with a descriptive approach developed in a Public Maternity in the municipality of Teresina-PI from August to October 2018. The study was attended by eight obstetrician nurses in the exercise of their function. Nurses with specialization in obstetrics and who directly assist pregnant women in the prepartum were included; excluding only those who were on vacation or leave while conducting the survey. A semi-structured script was used to collect the data and, for analysis, the Content Analysis technique was applied. It was evidenced that nurses work broadly from admission, guiding the process of labor and its phases, to the care exercised during the pre-delivery stimulating so that the pregnant woman has rapid dilation and with decreased pain. It is necessary that the nurses exercise principles of humanization of care, value the reception, the practice of listening to the patient and the respectful relationship between professionals / clients. The study is expected to contribute to the expansion of obstetrical nurses' activity, and to the quest for quality of services, especially with full care of women during labor.